Pengaruh Lingkungan Sekolah Terhadap Moral Siswa Di Madrasah Tsanawiyah Muhammadiyah 1 Pekanbaru - JP, Daisy (Tarunaedu: Journal of Education and Learning, 2025)
It was instigated by the indications that showing that there was an influence of of the School Environment toward students’ moral at Islamic Junior High School of Muhammadiyah 1 Pekanbaru. It was seen when the writer premalery research at Islamic Junior High School of Muhammadiyah 1 Pekanbaru. It was conducted on event semester in the academic. Subject ofthis research were all student of the eight and ninth grade. Object of this research was of the school environment toward student moral at Islamic Junior High School of Muhammadiyah 1 Pekanbaru. All student of eight and ninth grade amount 45 students was the sample. Sampling Jenuh was used for taking the sample. It was correlation research. Product moment formula was used for analyzing. Based on the data analysis and presentation about The Influence of the School Environment toward students’ moral at Islamic Junior High School of Muhammadiyah 1 Pekanbaru. It could be concluded that there was a significan influence between school environment and students’moral. Ic could be seen from the result 0.666 at 5% significant level and 1% (0.304<0.666>0.393).